Проектирование реактивных алгоритмов путем решения уравнений над автоматами - Чеботарев, А.Н. (Кибернетика и системный анализ, 2012)
Розглядається задача розв’язання нерівностей над автоматами, яка виникає при композиційному підході до проектування реактивних систем. Задача формулюється та розв’язується на рівні специфікацій автоматів логічною мовою L. Показано, як одержати максимальний розв’язок нерівності відносно операції синхронної композиції автоматів. Іл.: 3. Бібліогр.: 9 назв. The problem of solving inequalities over finite state machines (FSMs) is considered. This problem arises in the compositional approach to the design of reactive systems. The problem is formulated and solved at the level of FSM specifications in the logical language L. We show how to compute the maximal solution to the inequality with respect to the operation of synchronous composition of FSMs.